Three scenarios for the future of technology and strong democracy. - Barber, Benjamin R. (Political Science Quarterly)
There are at least three prospects for the future of technology and democracy that are within the domain of technological possibility. These are the Pangloss scenario, which is grounded in complacency and is simply a projection of current attitudes and trends; the Pandora scenario, which examines the worst possible case in terms of the inherent dangers of technological determinism; and the Jeffersonian scenario, which looks for the affirmative uses of the new technology in the nurturing of modern democratic life. The new technologies have the potential to improve lateral communication among citizens, can open access to information by all, and can offer citizens communication links across distances that once precluded direct democracy. However, unless there is clarity about the meaning of democracy and the type of democracy envisioned, technology is just as likely to retard as to enhance the civic polity.